Impact of Carbohydrate Counting Method during Pregnancy in Women with Pregestational Diabetes Mellitus: A Controlled Clinical Trial - Oliveira, Larissa Mello de; Belfort, Gabriella Pinto; Padilha, Patricia de Carvalho; Rosado, Eliane Lopes; Silva, Letícia Barbosa Gabriel da; Fagherazzi, Sanmira; Zajdenverg, Lenita; Zagury, Roberto Luís; Saunders, Claudia (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To evaluate the effect of the carbohydrate counting method (CCM) on glycemic control, maternal, and perinatal outcomes of pregnant women with pregestational diabetes mellitus (DM).Methods Nonrandomized controlled clinical trial performed with 89 pregnant women who had pregestational DM and received prenatal care in a public hospital in Rio de Janeiro, state of Rio de Janeiro, Brazil, between 2009 and 2014, subdivided into historic control group and intervention group, not simultaneous. The intervention group (n = 51) received nutritional guidance from the carbohydrate counting method (CCM), and the historical control group (n = 38), was guided by the traditional method (TM). The Mann-Whitney test or the Wilcoxon test were used to compare intra- and intergroup outcomes and analysis of variance (ANOVA) for repeated measures, corrected by the Bonferroni post-hoc test, was used to assess postprandial blood glucose.Results Only the CCM group showed a reduction in fasting blood glucose. Postprandial blood glucose decreased in the 2nd (p = 0.00) and 3rd (p = 0.00) gestational trimester in the CCM group, while in the TM group the reduction occurred only in the 2nd trimester (p = 0.015). For perinatal outcomes and hypertensive disorders of pregnancy, there were no differences between groups. Cesarean delivery was performed in 82% of the pregnant women and was associated with hypertensive disorders (gestational hypertension or pre-eclampsia; p = 0.047).Conclusion Both methods of nutritional guidance contributed to the reduction of postprandial glycemia of women and no differences were observed for maternal and perinatal outcomes. However, CCM had a better effect on postprandial glycemia and only this method contributed to reducing fasting blood glucose throughout the intervention.ReBEC Clinical Trials Database The present study was registered in the ReBEC Clinical Trials Database (Registro Brasileiro de Ensaios Clínicos, number RBR-524z9n).
Keywords: pregnancy; diabetes mellitus; prenatal care; nutrition therapy